2011
DOI: 10.1002/btpr.569
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early prenatal hypercapnia on the vascular network in the chorioallantoic membrane of the chicken embryo

Abstract: Over the last decade, the poultry sector has sought to develop novel ways to monitor chicken embryonic growth, health, and quality to control and optimize egg incubation conditions, particularly the concentration of dissolved gases (O(2), CO(2)). One of the parameters, which may change under different gas concentrations, is the angiogenesis in the chorioallantoic membrane (CAM), the organ for gas exchange of the chicken embryo. In this study, a newly developed methodology was used to quantify the angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Thus, studies that aimed at evaluating the effect of environmental factors in vascular development have taken advantage of this system in a manner that could not be achieved in mammalian systems. Exposure of CAMs to different degrees of CO2 [205] and O2 [206,68], for example, have demonstrated the impact of gases on vascular development. While hypoxia and hyperoxia will be discussed more in detail below, this constitutes a classical example of how the system can be exploited to clarify environmental effects on vascular growth.…”
Section: Cam As a Tool To Study Vascular Developmentmentioning
confidence: 99%
“…Thus, studies that aimed at evaluating the effect of environmental factors in vascular development have taken advantage of this system in a manner that could not be achieved in mammalian systems. Exposure of CAMs to different degrees of CO2 [205] and O2 [206,68], for example, have demonstrated the impact of gases on vascular development. While hypoxia and hyperoxia will be discussed more in detail below, this constitutes a classical example of how the system can be exploited to clarify environmental effects on vascular growth.…”
Section: Cam As a Tool To Study Vascular Developmentmentioning
confidence: 99%
“…However, other studies showed that the gradual increase of CO 2 concentration until day 10 of incubation promoted embryonic growth, reduced incubation time, increased hatchability (Gildersleeve et al, 1983;Bruggeman et al, 2008), and improved chick quality (Tona et al, 2007;, 2008. These results were associated with the development of the circulatory system and increased production of red blood cells, allowing greater O 2 uptake and energy conservation (Tazawa et al, 2002;Decuypere et al, 2006;Habermann et al, 2008;Verhoelst et al, 2011).…”
Section: Air Quality: O 2 and Co 2 Concentrationsmentioning
confidence: 99%
“…Furthermore, the absorption band of water at 970 nm is detectable. In previous research,8 we have observed that the density of the vascular network in the CAM, measured by the vascular fraction (VF), increases from ED 10 to 13, and from ED 13 to 16 8. Moreover, on ED 10 and 13, the hypercapnic group has a denser vascular network compared with the control group.…”
Section: Discussionmentioning
confidence: 85%
“…Increasing the CO 2 concentrations during early incubation, as in nature,7 seems to have positive effects. It affects the embryo weight, the hatching time, the time between internal pipping and hatch, and the angiogenesis in the chorioallantoic membrane (CAM) 8–11. The CAM is a well‐vascularized membrane which lies just underneath the eggshell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation